Analisis Optimasi Waktu dan Biaya Proyek Dengan Metode Time Cost Trade Off dan Fast Track Pada Pekerjaan Penanganan Longsor - Ashari, Nur Fitri (Jurnal Proyek Teknik Sipil, 2023)
In the Grand City Balikpapan area, a residential area is planned using a WTP (Water Treatment Plant) system for clean water supply. The project is planned to be completed in 12 weeks, but there is a delay in the project work so that it requires acceleration. The required objective is to optimize the time and cost in the implementation of the acceleration project and get a method or alternative that is in accordance with the project acceleration plan. The methods used in the acceleration of the Grand City Balikpapan WTP Area Landslide Handling Work Project in order to obtain the optimal time and cost are methods called Time Cost Trade Off and Fast Track. In Time Cost Trade Off method, there are three acceleration alternatives used, namely additional working hours, additional labor and additional heavy equipment. The acceleration time obtained based on the methods and alternatives used is 60 working days. The cost needed to complete the acceleration project by using Time Cost Trade Off method on the alternative of additional working hours (overtime) is Rp 664,593,423, while on the alternative of additional labor is Rp 644,856,028. The alternative of adding heavy equipment cannot be used in accelerating this project because the scope of the project is small for the use of a lot of heavy equipment. Then for the Fast Track method, it costs Rp 611,609,685, so the method used to accelerate the project is the Fast Track method by changing the working relationship.